SISTEM INFORMASI MANAJEMEN DALAM MENDUKUNG AKUNTABILITAS DAN PENGAMBILAN KEPUTUSAN DI LEMBAGA PENDIDIKAN ISLAM - Rizky Maulida (Jurnal Manajemen Pendidikan, 2025)
Objective: This study aims to examine the role of Management Information Systems (MIS) in supporting accountability and decision-making in Islamic educational institutions. Using a qualitative method with a meta-analysis approach, this research reviews, compares, and synthesizes various research findings obtained from journals, books, and scientific reports. This approach provides a comprehensive overview of patterns, key findings, and conceptual relationships related to the implementation of MIS across different contexts of Islamic educational institutions. The findings indicate that MIS makes a significant contribution to enhancing accountability through the presentation of accurate, structured, and easily accessible data, enabling reporting processes to become more transparent and accountable to stakeholders. MIS is also proven to support data-driven decision-making by providing relevant information that helps institutional leaders formulate policies, plan programs, and conduct continuous evaluations. Novelty: The novelty of this study lies in its approach, which positions MIS not merely as an administrative tool but as a system capable of simultaneously strengthening accountability and the quality of decision-making. Through meta-analysis, this research provides a deeper understanding of the role of MIS while offering a new perspective by incorporating Islamic values such as trustworthiness (amanah), honesty, and consultation (musyawarah) in its use.